Isolasi dan Identifikasi Enterobacter sakazakii pada Susu Mentah dan Produk Susu Segar di Daerah Istimewa Yogyakarta - Tri Yahya Budiarso; Hutri Catur Sad Winarni (Jurnal Sain Veteriner, 2016)
Enterobacter sakazakii is an opportunistic pathogen that causes infections such as necrotizing enterocolitis, bacteremia, and meningitis which, in many cases, have been associated with the consumption of powdered infant formula. Raw milk has been considered to be a potential source of contamination. The aim ofthis study was to detect and identify the presence of E. sakazakii in raw milk from local farms and fresh dairy products sold by street vendors and cafés in the Special Region of Yogyakarta. A total of 80 milk samples were cultured in Enterobacterriaceae Enrichment Broth. The cell cultures were then enumerated on Tryptone Soya Agar and Chromocult Coliform Agar. For the isolation of suspect colonies, Chromogenic Druggan-Forsythe-Iversen (DFI) Agar was used. Presumptive colonies of E.sakazakii were characterized biochemically using API20E and molecularly through the amplification of the 16S rRNA gene using primer pairs 16_SUNI-L/Saka-2b and ESA-1/16_SUNI-R. Based on the α-glucosidase test of DFI Agar, only 9 isolates out of the 80 samples wereidentified as suspected E.sakazakii. Biochemical and molecular identification suggested that 5 isolates resulted positive for E.sakazakii, while the other 4 were Panthoea spp1.